PDCL3 promotes the vasculogenic mimicry of glioma-associated mesenchymal stem cells through VEGFR-2 in glioma environment - Yihao Wang; Zhen Liu; Dongye Yi; Sujie Gu; Zesheng Peng; Haofei Wang; Peng Lv; Wei Xiang; Xiaobing Jiang; Peng Fu (iScience)
Summary: Glioma-associated mesenchymal stem cells (GA-MSCs), as a critical component of the glioma microenvironment, play an essential role in the development and invasion of glioma. Recent studies have shown that GA-MSCs can differentiate into pericytes under certain conditions, thereby promoting angiogenesis. However, the biological properties and molecular mechanisms underlying this process remain poorly understood. In the glioma microenvironment, our data revealed that the upregulation of Phosducin-like 3 (PDCL3) in GA-MSCs influences the expression of the downstream Vascular Endothelial Growth Factor Receptor 2 (VEGFR-2) and pericyte markers, indicating a transformational relationship between GA-MSCs and pericytes. Furthermore, the vascular mimicry ability of co-cultured GA-MSCs and Human Umbilical Vein Endothelial Cells (HUVECs) is also significantly affected. Glioma induces the upregulation of PDCL3 expression in GA-MSCs, facilitating their transformation of GA-MSCs into pericytes and promoting tumor angiogenesis. These findings suggest that PDCL3 in GA-MSCs could serve as a potential target for anti-angiogenesis therapy in glioma.